Analisis Pola Asuh Wanita Karir terhadap Perkembangan Anak Usia Dini dan Kehidupan Rumah Tangga - Omega Bia; Hendrik A. E. Lao (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
The increase in women's participation in the workforce has a significant impact on early childhood parenting patterns and the dynamics of household life. This research aims to analyze how career women apply parenting styles to young children and how this affects child development and the balance of home life. The study uses a mixed methods approach with an explanatory sequential design, starting with a quantitative approach followed by a qualitative approach. The goal is to gain a comprehensive understanding of the parenting styles of career women, early childhood development, and household life. The research population includes career women who have young children at the GMIT Horeb Perumnas Congregation in Kupang City. The research results show that although career women face time limitations, they tend to adopt a democratic parenting style supported by caregivers or partners. Child development can remain optimal if communication patterns and emotional involvement are maintained. However, challenges arise in terms of emotional closeness and quality time. Therefore, adaptive strategies and family support are needed to maintain a balance between career and maternal roles.